Post-Covid Schooling Future Alternatives to the Global Normal - Harber, Clive; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This book questions the consensus that contemporary formal schooling is of clear cut and undoubted benefit to pupils. During lockdowns caused by the global COVID-19 pandemic, governments and various other actors have been trying to get children and young people back into school as quickly as possible. While there are any numerous beneficial aspects of schooling, the book asks whether accepted models and practices of schools should change in a post-COVID world. By critically examining the everyday nature of 'normal' schooling, the book demonstrates that many aspects of schooling are not necessarily beneficial to pupils, and can be directly harmful: in doing so, the author imagines a future of schooling that could better support and benefit its students. Clive Harber is Emeritus Professor of International Education at the University of Birmingham, UK. His research interests include education for peace and democracy on the one hand, and education for violence and authoritarianism on the other.
Chapter 1. Normal, Everyday Schooling : preserving the status quo or making matters worse? -- Chapter 2. School As an Organisation: Compulsion, Control and Corruption -- Chapter 3. Daily Rules and Routines -- Chapter 4. Punishment -- Chapter 5. Examinations and Testing -- Chapter 6. School Uniform and Uniformity -- Chapter 7. The Journey to and from School -- Chapter 8. School Buildings (and Grounds) -- Chapter 9. Post-covid Schooling?.
Keywords: Schools; Alternative Education; Inclusive education; Teaching; School and Schooling; Alternative Education; Inclusive Education; Pedagogy